Local Wisdom as a Social Security Instrument for the Poor in North Maluku, Indonesia - Amin, Safrudin; Ahmad, Irfan; Maricar, Farida; Abdulrahman, Safrudin (Universitas Negeri Semarang, 2019)
The studies of cultural revitalization, local wisdom, and social security are often separated and seems unconneted. This article aims at connecting these domains through ethnographic research and document analysis of the phenomena in revitalization of local wisdom called bari to strengthen the social security of the poor in North Maluku. Revitalization activies like raising funds from public not from government budget to build hundreds of decent housing for the poor is interesting issue to study. The three main concerns of this article are socio-cultural factors that encourage the birth of this movement, the activities and achievements of these revitalization movements, and the typical characteristics of local wisdom as a result of revitalization that distinguishes it from its original form. The findings presented in this article can contribute to academic discourse in the domains of local wisdom, cultural revitalization, and social security. The more important of this finding is to construct arguments about the existence of a bridge between local wisdom, revitalization, and social security.